HUBUNGAN KADAR C-REACTIVE PROTEIN DENGAN DERAJAT KEPARAHAN PASIEN COVID-19 YANG DIRAWAT INAP DI RUMAH SAKIT - Nuswantoro, Ari; Perdede, Lusi Hernawati; Aulia, Annisa Syafa; Aditia, Aditia (Poltekkes Kemenkes Bandung, 2022)
Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) can appear with a varied clinical spectrum, ranging from no symptoms, mild illness, moderate illness, to severe illness. The high mortality rate is closely related to the severity of the disease. One of the laboratory parameters that is thought to be related to the severity of COVID-19 is C-Reactive Protein (CRP). This study aimed to determine the relationship between CRP values and the severity of COVID-19 patients. This research has an analytical observational design with a cross-sectional approach. The samples were COVID-19 patients with moderate and severe symptoms who were hospitalized at RSUD dr. Soedarso West Kalimantan in January - December 2021. The sampling technique was total sampling to obtain medical record data which included CRP values and patient severity levels so that 49 data were obtained. The results showed that 8 respondents (16.3%) had CRP levels of 0.8 mg/dL, 24 respondents (49%) had CRP levels of 1.6 mg/dL, 9 respondents (18.4%) had CRP levels of 3 .2 mg/dL and 8 respondents (16.3%) had CRP levels of 6.4 mg/dL. Based on Kendall's tau-b statistical test, a significance value of 0.001 <0.05 was obtained, which means there is a significant relationship between CRP levels and severity. The correlation coefficient value of 0.708 shows a strong correlation coefficient between CRP levels and severity. This proves that the higher the CRP levels of COVID-19 patients found, the more severe the degree of disease that may be suffered by these patients, so there is a close relationship between CRP levels and the degree of disease of COVID-19 patients.